Geographical Distribution of Dairy Cattle in Boyolali - Priyana, Yuli; Simoen, Soenarso; Suyono, Suyono (Forum Geografi, 1999)
The researcch about the geographic distribution of diary cattle breeders, is held in Subdistrict of Selo, Cepogo, Musuk, Boyolali, Mojosongo, Teras, and Banyudono, Boyolali regency. This research aims to investigate potential areas for dairy attle breeding and the physical factors (availability of groundwater, average temperature, altitude, accesibility) that contribute most to the density of cattle in the research site. In addition, it investigates the differences m water supply for dairy cattle breeding and the ratio of income to cost at every morphological units as well as the effect of the amount of water supply on milk production and the effect of the Ca content of groundwater on the density of dairy cattle. The methods use in the research is survey method. The data colleted in the research consist of 200 primary data of the respondents taken from head of dairy cattle breeders families using a questionnare. Secondary data are obtained from related agencies, reference books and other authorized source dealing with the research yopic. In order to find out the differences in water supply for dairy cattle breeding and the ratio of income to cost, a statistical measurenment with Anova test is carried out. A multiple regression test is used to find out the effects of the availability of groundwater, altitude, average temperature, and accesibility on the density of dairy cattle. A simple regression test is used to find out the effects of water supply on milk producctin and the Ca sontent of groundwater on the density of dairy cattle.The result of the research indicate that the researchÂ  site consist of four morphological units, namely the Volcanic slope, Volcanic foot, fluvio Volcanic foot, fluvio volcanic plain. The potential areas for dairy cattle breeding are situated at an altitude of 700 meters, temperature 17o C â 21o C especially the areas in the subdistrict of Selo and Cepogo. The result of the statistical test indicate that the most differences in the amount of water supply for dairy attle breeding as well as in the rasio between income and cost among morphological units. Water supply for dairy cattle breeding has no effect on milk production, whereas the Ca content of groundwater has no effect on the density of dairy cattle.